Percepções de licenciandos sobre o estágio supervisionado remoto em tempos de pandemia - Bossolan, Danielle Cristine (Universidade Federal de São Carlos, 2022)
As a fundamental component of the curriculum in undergraduate courses, the subject of supervised internship aims to provide students in initial teacher-training the confluence of theoretical and practical experiences in the school environment, that being a field of research and knowledge (PIMENTA; LIMA, 2006). Acknowledging the teaching activity as work requires the understanding that numerous aspects essential to "being a teacher" evolve and change over time and with experience, accepting the internship as the primary space in which such ideals and skills first emerge. In order to conduct this research, a historical-temporal cut is made with the purpose of investigating, exclusively, the internship done remotely during the COVID-19 pandemic. We intend to identify and understand the perceptions of a group of undergraduates about this particular period, analyzing experience reports available in open acess environments. At first, this study presents conceptions related to supervised internship, to the context of emergency remote teaching and to experience reports, which served as a basis for the later stage in our research, in which we qualitatively analyze what we found of opinions on remote supervised internships made by the students. To that end, this is an early exploratory study that aims to contribute to the development of understandings of what this period of social isolation was like for those going through teacher-training processes.
Perceptions of undergraduates about the remote supervised internship in times of a pandemic
Keywords: Estágio supervisionado; Ensino remoto emergencial; Estágio supervisionado remoto; Relatos de experiência; Supervised internship; Emergency remote teaching; Remote supervised internship; Experience reports; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS; LINGUISTICA, LETRAS E ARTES